Bronchiectasis consequent upon foreign body retention - Kürklü, E. U. (1973)
Kürklü, E. U., Williams, M. A., and le Roux, B. T. (1973).Thorax, 28, 601-602. Bronchiectasis consequent upon foreign body retention. A series of patients in whom bronchiectasis was related to long retention of an intrabronchial foreign body is reported. The surgical rules which apply to management of intrabronchial foreign bodies by bronchotomy are restated.